Development and delivery of an exercise intervention for rheumatoid arthritis: strengthening and stretching for rheumatoid arthritis of the hand (SARAH) trial. - Heine, P; Williams, M; Williamson, E; Bridle, C; Adams, J; O'Brien, A; Evans, D; Lamb, SE; Sarah, T (2012)
This paper describes the development and implementation of a hand exercise intervention for rheumatoid arthritis (RA) as part of a large multi-centred randomised controlled trial in a U.K. National Health Service (NHS) setting. Participants are eligible if diagnosed with RA according to American College of Rheumatology criteria, have a history of disease activity, functional deficit or impairment in the hand and/or wrist, and have been on a stable medication regime for at least 3 months. The intervention development was informed by the current evidence base, published guidelines, clinician and expert opinion, and a pilot study. The exercise programme targets known, potentially modifiable physical impairments of the hand with 5 exercise sessions and a home exercise component over a 12 week period. The intervention will be provided to 240 participants along with usual care. A further 240 will receive usual care only as part of the control arm. Specific details of the treatments delivered are described. [ISRCTN no: 89936343]. Copyright © 2011 Chartered Society of Physiotherapy. Published by Elsevier Ltd. All rights reserved.